P223 Analysis of abductor pollicis brevis and orbicularis oris muscles representation of full face transplantation patients using TMS. Issue 9 (September 2017) - Gök, Kadir; Döğer, Ela Naz; Göztepe, Mehmet Berke; Gök, Melahat; Uysal, Hilmi; Özkan, Özlenen; Özkan, Ömer; Şenol, Utku; Doğan, Ebru Apaydin; Barçin, Ebru; Bilge, İnci; Şavkliyildiz, Ayhan; et al.
Abstract : Facial transplantation is defined as transfer of facial tissue from a donor to a patient who has suffered facial loss as a result of total denervation. Loss of facial tissue in the patient's transplant history is important for synaptic change. Our study aims to develop neurophysiological approaches by defining the change of motor representations in the brain. In this study, Transcranial Magnetic Stimulation (TMS) is used to create Orbicularis Oris (O.Oris) and Abductor Pollicis Brevis (APB) muscles representation maps in facial transplant cases. Control group is established to identify brain presentation changes in facial transplant cases. The position, amplitude and latency values of muscular action potentials induced by magnetic stimulation are determined by signal processing methods. The results are mapped on 3-D human model. In the first case, the hot spot is identified as FC5 (4.66 mV to 5 ms) in the face mapping. When the face mapping of the patient is compared with the control group, the hot spot amplitude value is acquired as 64.25% and the latency value is 1.01% higher. In this case, the facial responses become more lateral. In the second case, the hot spot is found as AF7 (1.41 mV to 5.40 ms), and 50.29% decreases in amplitude value and 9.09% increases in latency value occur in the face mapping. It is observed that the facial responses are enlarged anteriorly and hand responses are detected in the face area. The results which denote the existence of the brain plasticity in the face transplant patients can be evaluated in the planning of rehabilitation processes. This study is supported byTUBITAK with215E012 project number.